Anti-lung Cancer Mechanism of Quercetin Based on Network Pharmacology and Experimental Validation - Yi WANG; Xiaofang PU (Shipin gongye ke-ji)
Objective: To investigate the potential mechanisms of quercetin in the treatment of non-small cell lung cancer (NSCLC) and validate them through molecular biology experiments. Methods: Target prediction for quercetin was performed using the SwissTargetPrediction and DrugBank databases, while NSCLC disease targets were collected from GeneCards and TTD databases. Target mapping was performed to identify the targets of quercetin in treating NSCLC. The protein-protein interaction (PPI) network was obtained from the STRING database and analyzed using Cytoscape 3.7.2 for visualization. Target enrichment analysis was carried out using the DAVID database, along with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Additionally, this study employed molecular docking to validate core targets and utilized the PLIP platform for combined analysis of binding site mechanics data. The impact of quercetin on the proliferation of A549 cells was assessed through cell experiments, and core targets were validated using qRT-PCR and Western blot. Results: Network pharmacology analysis revealed that quercetin could regulate 126 targets, with 49 potential targets for NSCLC treatment. The core pathway identified was the PI3K-Akt signaling pathway, with core targets being PI3K, Akt, and GSK-3β. Molecular docking experiments preliminarily demonstrated strong binding affinity between quercetin and the three core targets. Cellular experiments indicated that quercetin intervention in low, medium, and high doses significantly inhibited the proliferative activity of A549 cells after 72 hours (P<0.01) and downregulated the mRNA expression levels of PI3K, Akt, and GSK-3β (P<0.05), as well as protein expression trends. Conclusion: This study analyzed and predicted the potential active mechanisms of quercetin in treating NSCLC. Experimental validation suggested that quercetin might exert its anticancer effects by inhibiting the PI3K/Akt/GSK-3β signaling pathway.